2003
DOI: 10.1074/jbc.m301562200
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitor Thiomandelic Acid Binds to Both Metal Ions in Metallo-β-lactamase and Induces Positive Cooperativity in Metal Binding

Abstract: Thiomandelic acid is a simple, broad spectrum, and reasonably potent inhibitor of metallo-␤-lactamases, enzymes that mediate resistance to ␤-lactam antibiotics. We report studies by NMR and perturbed angular correlation (PAC) spectroscopy of the mode of binding of the R and S enantiomers of thiomandelic acid, focusing on their interaction with the two metal ions in cadmium-substituted Bacillus cereus metallo-␤-lactamase. The 113 Cd resonances are specifically assigned to the metals in the two individual sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 41 publications
7
43
0
1
Order By: Relevance
“…bound to sites DCH and D3H, respectively, differing significantly from the resonance here reported (52,53). The 115 ppm resonance observed for 113 Cd(II)-GOB-18 agrees well with experimental 113 Cd NMR data giving a resonance at 120 ppm for carboxypeptidase A (54), presumably with a N 2 O 3 coordination sphere (two histidines, one water, and a bidentate carboxylate) and also with theoretical predictions (55).…”
Section: Substratesupporting
confidence: 78%
“…bound to sites DCH and D3H, respectively, differing significantly from the resonance here reported (52,53). The 115 ppm resonance observed for 113 Cd(II)-GOB-18 agrees well with experimental 113 Cd NMR data giving a resonance at 120 ppm for carboxypeptidase A (54), presumably with a N 2 O 3 coordination sphere (two histidines, one water, and a bidentate carboxylate) and also with theoretical predictions (55).…”
Section: Substratesupporting
confidence: 78%
“…The results for thiomandelate with the CphA enzyme also provided unexpected new information on inhibition of the CphA enzyme. This inhibitor induced an increase of the affinity for binding of a second zinc ion in the complexed compared to uncomplexed enzyme, analogous to observations on the inhibition of the mono-cadmium form of the BcII enzyme [8], where thiomandelate induced conversion of the mono-to the dicadmium enzyme. Thus, the present work indicates that the differences in the stoichiometry of metal binding by the MBLs may be more subtle than previously appreciated.…”
Section: Discussionsupporting
confidence: 49%
“…The substrate profile of the family, coupled with the different metal stoichiometries, poses a challenge for the design of clinically useful inhibitors. Mercaptocarboxylates have been identified as competitive inhibitors of the MBLs [7] and structures of the MBLs reveal that the thiol group of inhibitor is chelated by both zinc ions [8,9].The aim of this work was to investigate the utility of ESI-MS for the screening of MBL inhibitors, by direct analysis of enzyme:metal:inhibitor complexes. Precedents for the use of ESI-MS to directly investigate…”
mentioning
confidence: 99%
“…A combined Cd 113 -NMR and PAC spectroscopic study of the enzyme at various cadmium/enzyme stoichiometries resulted in data which suggested that it was only possible to obtain the binuclear inhibited enzyme and not a mononuclear inhibited species. The inevitable conclusion of the authors was that the presence of thiomandelate induced positive cooperativity of cadmium binding for BcII [135]. The latter findings reinforce the question how many zinc ions are required and what is the physiologically relevant enzyme species to be considered as a target in inhibitor design.…”
Section: Inhibition Of Metallo-b B-lactamasessupporting
confidence: 48%